Whole Blood Profiling of Bacillus Calmette–Guérin-Induced Trained Innate Immunity in Infants Identifies Epidermal Growth Factor, IL-6, Platelet-Derived Growth Factor-AB/BB, and Natural Killer Cell Activation - Smith, Steven G.; Kleinnijenhuis, Johanneke; Netea, Mihai G.; Dockrell, Hazel M. (Frontiers in Immunology, 2017)
Vaccination of infants with BCG activates both the innate and adaptive arms of the immune response. The anti-mycobacterial effects of these responses most likely account for the ability of BCG to protect against childhood forms of tuberculosis. There is also evidence for a heterologous protective effect of BCG vaccination against tuberculosis-unrelated mortality in low birth weight infants. A possible mechanism of action of this effect, the induction of trained innate immunity, has been demonstrated when cells from BCG vaccinated adults are re-stimulated in vitro with non-related microbial stimuli. Our aim was to examine an extensive panel of secreted immune biomarkers to characterise the profile of trained innate immunity in infants. Stimulation of whole blood for forty-eight hours was performed 4 months after BCG vaccination, or in control unvaccinated infants. Stimulants were LPS; Pam3Cys; heat-killed Candida albicans, Staphylococcus aureus, Escherichia coli and a lysate of Mycobacterium tuberculosis. Culture supernatants were tested for secreted cytokines and chemokines by 42-plex bead array and monocytes and natural killer cells assessed for expression of activation markers by flow cytometry. BCG-vaccinated infants displayed increases in 11 cytokines and chemokines in response to different non-specific innate immunity stimuli: epidermal growth factor (EGF); eotaxin; IL-6; IL-7; IL-8; IL-10; IL-12p40; monocyte chemotactic protein-3; macrophage inflammatory protein-1alpha; soluble CD40 ligand and platelet-derived growth factor (PDGF)-AB/BB. Although each stimulant induced a distinct response profile, three analytes, EGF, IL-6 and PDGF-AB/BB, were commonly higher after stimulation with Pam3Cys, C. albicans and S. aureus. Conversely, certain cytokines such as interferon gamma-inducible protein-10, IL-2, IL-13, IL-17, GM-CSF and GRO were suppressed in BCG-vaccinated infants, while no increases in TNFalpha or IL-1beta production were detected. We did not observe a concomitant, BCG-associated change in monocyte surface activation markers in response to non-specific stimuli, but we detected a significant increase in CD69 expression on natural killer cells in response to Pam3Cys. Pam3Cys-induced natural killer cell activation correlated with the magnitude of IL-12p40 and IL-10 responses to the same stimulant. This study reveals a novel cytokine/chemokine biomarker signature of BCG-induced trained innate immunity in infants and the involvement of natural killer cells in these responses.